2021
DOI: 10.1007/s10882-021-09829-2
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Adults with Tourette’s Syndrome: “Never Laugh at Other People’s Disabilities, Unless they have Tourette’s—Because How Can You Not?”

Abstract: Tourette’s syndrome (TS) is a condition that has been stigmatised and mocked in contemporary society, yet little is known about the subjective experience of those directly affected by it. Guided by Public and Patient Involvement (PPI) a mixed method design was used for this study to explore the experience of stigma in adults living with TS in the UK. A total of one hundred and ninety-nine adults participated in a cross-sectional online survey using an adapted version of the Discrimination and Stigma Scale (DIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 66 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…The experience of being bullied for having TS is reported commonly in extant literature (e.g., Malli et al, 2021;Smith et al, 2015). Our findings parallel past studies, as participants reported experiencing bullying primarily in childhood, with an occasional mention of its presence in adulthood.…”
Section: General Bullyingsupporting
confidence: 87%
See 3 more Smart Citations
“…The experience of being bullied for having TS is reported commonly in extant literature (e.g., Malli et al, 2021;Smith et al, 2015). Our findings parallel past studies, as participants reported experiencing bullying primarily in childhood, with an occasional mention of its presence in adulthood.…”
Section: General Bullyingsupporting
confidence: 87%
“…In two additional studies, one that involved interviewing 16 adults with TS (Malli et al, 2019) and the other performing a mixed-methods approach including a survey of 199 adults and interviews with 20 (Malli & Forrester-Jones, 2021), researchers examined the "social and personal cost of living with TS during adulthood" (Malli et al, 2019, p. 819). Their participants reported several social challenges including rejection, marginalization, victimization, the trivialization of TS through humor, prolonged and intrusive staring, and being asked to leave public places (Malli et al, 2019;Malli & Forrester-Jones, 2021). Malli and colleagues specified 21 domains of "enacted discrimination," including in educational settings (75.4% of participants), in social life (71.4%), on public transport (60.8%) and with respect to employment (54.3%) (Malli & Forrester-Jones, 2021, p. 10).…”
Section: Ts Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, many children with TS are teased (Debes, Hjalgrim, and Skov, 2010), victimised or rejected by their peers (Packer, 2005; Storch, Merlo, Lack, et al., 2007; Zinner, Conelea, Glew, et al., 2012). Crucially, a recent study identified a staggering three‐quarters of adults with TS had experienced stigma in education settings (Malli and Forrester‐Jones, 2021). Therefore, children with TS's ability to socialise and make friends at school can be just as demanding as the academic aspects they encounter.…”
Section: Introductionmentioning
confidence: 99%